Multiple time points of transcriptome analysis revealed altered genes involved in maintaining hibernation in the hypothalamus of Tamias sibiricus - Zhang, Tian; Yang, Chao; Guo, Yaxiu; Xu, Zihan; Zhao, Minbo; Wu, Feng; Zhang, Hongyu; Wang, Hailong; Sui, Xiukun; Jiang, Siyu; He, Rongqiao; Dai, Zhongquan; et al. (Frontiers in Neuroscience, 2024)
Hibernation, an adaptive mechanism to extreme environmental conditions, is prevalent among mammals. Its main characteristics include reduced body temperature and metabolic rate. However, the mechanisms by which hibernating animals re-enter deep sleep during the euthermic phase to sustain hibernation remain poorly understood. We selected the Tamias sibiricus as a model organism and conducted transcriptomic sequencing of its hypothalamus at multiple time points throughout hibernation. Through the strategies of gene set filtering and intersection analysis, we effectively filtered out redundant data, identifying a subset of genes whose expression was downregulated during the euthermic phase potentially inducing re-enter deep sleep, thereby maintaining the periodic cycles of torpor and arousal. These cycles are crucial for sustaining the overall hibernation process. Notably, genes associated with sodium and potassium ion channels were significantly enriched. Specifically, potassium ion-related genes such as Kcnc1, Kcna2, Kcng4, and Kcna6, along with sodium ion-related genes such as Scn1a and Hcn2, were markedly downregulated. qRT-PCR validation of four of these genes (Kcnc1, Kcna6, Scn1a, and Hcn2) confirmed significant downregulation during the euthermic phase compared to the deep sleep phase, further supporting our transcriptomic findings. This study provides novel insights into the hypothalamic transcriptome dynamics at various hibernation stages. Although the functional roles of these genes require further investigation, our findings lay the groundwork for future studies to elucidate the molecular mechanisms underlying hibernation.